Treatment Seeking Patterns among Dengue Fever Patients: A Qualitative Study - Krisnian, Tharani; Alisjahbana, Bachti; Afriandi, Irvan (Althea Medical Journal, 2017)
Background: Incidence of dengue fever is increasing drastically and has become a major public health problem globally. The reason patients are late in seeking medical treatment should be identified in order to prevent complications which can be avoided to produce a good prognosis. This study was conducted to find the pattern of treatment seeking behaviour among dengue fever patients and their influencing factors using a health utilisation model. Methods: Data on health seeking behaviour were collected among the dengue fever patients who were admitted to Dr. Hasan Sadikin General Hospital Bandung from SeptemberâOctober 2014. The data were collected through in-depth interview with patients who were diagnosed with dengue fever and dengue haemorrhagic fever. All the interviews were recorded using an audio recorder. The recordings were transcribed and then translated into English and analyzed using thematic analysis.Results: Nine patients were interviewed. The age of the patients ranged between 17 to 46 years.Â  Altogether 7 patterns were identified with patients treatment seeking behavior. Most of them took longer steps to reach adequate care with blood examination. These longer steps, caused by lack of facilities to perform blood test in primary health care facilities, no bed for admission and also low skills of health care providers in diagnosing patients. The primary health care facility played an important role in the delay of patients acquiring definite care for their dengue fever.Conclusions: Health care seeking behavior is hampered by the inadequacy of primary health care facilities to provide adequate services to dengue patients.Â